30.8k views
0 votes
3(1−9a)+22a=2(2a−9)−15
i need a step by step explanation please

2 Answers

2 votes

Answer:

a = 4

Explanation:

first distrubute the 3 and then 2 in the equations to whatever is inside the parantheses:

3 ( 1-9a) + 22a = 2(2a-9) -15

3 - 27a + 22a = 4a - 18 - 15

then combine the terms:

3 - 5a = 4a -33

then isolate the variables and constants to one side, for example move the 5a to the right side of the equation and move the 33 to the left side of the equaiton and then simplfy

36 = 9a

divide both sides by 9

a = 4

User Aryanm
by
5.0k points
0 votes

Answer:a=4

Explanation:

Expand the brackets. Collect like terms. Get the same values on each side so it’s easier to isolate a. Divide 9 from 9a so that u get a by itself and this gives u the answer if 36/9 or 4.

3(1−9a)+22a=2(2a−9)−15 i need a step by step explanation please-example-1
User Simon Sanderson
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.